2013
DOI: 10.1083/jcb.2033oia132
|View full text |Cite
|
Sign up to set email alerts
|

Dual leucine zipper kinase is required for excitotoxicity induced neuronal degeneration

Abstract: Excessive glutamate signaling is thought to underlie neurodegeneration in multiple contexts, yet the pro-degenerative signaling pathways downstream of glutamate receptor activation are not well defined. We show that dual leucine zipper kinase (DLK) is essential for excitotoxicity-induced degeneration of neurons in vivo. In mature neurons, DLK is present in the synapse and interacts with multiple known postsynaptic density proteins including the scaffolding protein PSD-95. To examine DLK function in the adult, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 28 publications
6
50
0
Order By: Relevance
“…Intriguingly, we identified several genes that specifically enhanced neuronal survival when knocked down, including MAP3K12 (encoding dual leucine zipper kinase DLK), MAPK8 (encoding Jun kinase JNK1), CDKN1C (encoding the cyclin-dependent kinase inhibitor p57) and EIF2AK3 (encoding the eIF2alpha kinase PERK) (Table S1). A pathway involving DLK, JNK and PERK has previously been implicated in neuronal death (Ghosh et al, 2011;Huntwork-Rodriguez et al, 2013;Larhammar et al, 2017;Miller et al, 2009;Pozniak et al, 2013;Watkins et al, 2013;Welsbie et al, 2013), validating our approach.…”
Section: Introductionsupporting
confidence: 78%
“…Intriguingly, we identified several genes that specifically enhanced neuronal survival when knocked down, including MAP3K12 (encoding dual leucine zipper kinase DLK), MAPK8 (encoding Jun kinase JNK1), CDKN1C (encoding the cyclin-dependent kinase inhibitor p57) and EIF2AK3 (encoding the eIF2alpha kinase PERK) (Table S1). A pathway involving DLK, JNK and PERK has previously been implicated in neuronal death (Ghosh et al, 2011;Huntwork-Rodriguez et al, 2013;Larhammar et al, 2017;Miller et al, 2009;Pozniak et al, 2013;Watkins et al, 2013;Welsbie et al, 2013), validating our approach.…”
Section: Introductionsupporting
confidence: 78%
“…Pathway analyses of the cerebellum data showed that the genes co-regulated with Jun mRNA were enriched in basic metabolic pathways, suggesting a DLK-mediated link between synaptic function and metabolism. These data are consistent with the strong correlation we observed between p-c-jun and synaptophysin, and work in mice and invertebrates demonstrating a role for DLK in regulating synaptic strength (16). No gross changes in motor function or ambulatory behavior after long-term conditional DLK knockdown has been reported, thus the impact on DLK signaling on cerebellar physiology remains unknown.…”
Section: Discussionsupporting
confidence: 90%
“…In Drosophila and C. elegans, the DLK orthologs wallenda (Wnd) and DLK-1 regulate presynaptic function and morphology at the neuromuscular junction (14) and limit synaptic strength (15). However, adult somatic knockout of DLK in mice revealed no CNS phenotype other than resistance to various neuronal insults and a modest increase in post-synaptic evoked potentials in the hippocampus (16).…”
Section: Introductionmentioning
confidence: 99%
“…164,165 Recent studies suggest that DLK plays a central role as a regulator of neuronal degeneration. [166][167][168] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 However, all of these approaches require innovative strategies in inhibitor design combining expertise in classical medicinal and organic chemistry with competences in chemical biology and biotechnology. Moreover, novel cellular and in vitro assays will have to be established to enable the development of such inhibitors and to assess their clinical potential.…”
Section: Conclusion and Perspectivementioning
confidence: 99%